2023
DOI: 10.1108/bfj-01-2023-0080
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the SDGs by social economy enterprises in the agrifood sector

Juan Lafont-Torio,
Esther Calderon-Monge,
Domingo Ribeiro-Soriano

Abstract: PurposeAchieving the Sustainable Development Goals (SDGs) is a global initiative that is becoming increasingly important in the industrial and service sectors. This paper analyses how the SDGs are being implemented in the agrifood supply chain by social economy enterprises.Design/methodology/approachCase study methodology was used to understand how companies implement the SDGs. Semi-structured interviews were conducted with managers from two cooperatives in the agrifood sector.FindingsThere are no differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…While SDGs have been more widely adopted by many industries, agriculture has somewhat lagged. The work of Lafont-Torio et al (2023) has demonstrated that SDG adoption in agriculture is both feasible and as easy to achieve as other industries. Sustained government and NGO support is required, with strong collaborative links between public and private sectors, in order to minimize negative impacts and maximize innovation.…”
Section: A Greener Approachmentioning
confidence: 99%
“…While SDGs have been more widely adopted by many industries, agriculture has somewhat lagged. The work of Lafont-Torio et al (2023) has demonstrated that SDG adoption in agriculture is both feasible and as easy to achieve as other industries. Sustained government and NGO support is required, with strong collaborative links between public and private sectors, in order to minimize negative impacts and maximize innovation.…”
Section: A Greener Approachmentioning
confidence: 99%